2018
DOI: 10.1007/s12038-018-9815-9
|View full text |Cite
|
Sign up to set email alerts
|

Profile of pterostilbene-induced redox homeostasis modulation in cardiac myoblasts and heart tissue

Abstract: This study was designed to investigate the effect of pterostilbene (PTS) on cardiac oxidative stress in vitro, as this is a simple and promising methodology to study cardiac disease. Cardiac myoblasts (H9c2 cells) and homogenised cardiac tissue were incubated with the PTS and cyclodextrin (PTS ? HPbCD) complex for 1 and 24 h, respectively, at concentrations of 50 lM for the cells and 25 and 50 lM for cardiac tissue. The PTS ? HPbCD complex was used to increase the solubility of PTS in water. After the pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The concentration of collagen in the heart tissue is significantly increased ( Yin et al, 2012 ; Han et al, 2017 ). PTS has been shown to inhibit or reduce the production of fibrosis in myocardial ischemia and reperfusion, liver injury and lung injury ( Lv et al, 2015 ; Couto et al, 2018 ; Kosuru et al, 2018 ; Lacerda et al, 2020 ; Zhang et al, 2021 ). In this article, we found that the fibrosis level in the myocardial tissue after PTS treatment has been effectively controlled by the fibrosis markers collagen I and collagen III and Masson.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of collagen in the heart tissue is significantly increased ( Yin et al, 2012 ; Han et al, 2017 ). PTS has been shown to inhibit or reduce the production of fibrosis in myocardial ischemia and reperfusion, liver injury and lung injury ( Lv et al, 2015 ; Couto et al, 2018 ; Kosuru et al, 2018 ; Lacerda et al, 2020 ; Zhang et al, 2021 ). In this article, we found that the fibrosis level in the myocardial tissue after PTS treatment has been effectively controlled by the fibrosis markers collagen I and collagen III and Masson.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of reactive oxygen species (ROS) was estimated with the fluorescent probe 2,7-dichlorodihydrofluorescein diacetate (DCFHDA), as previously described. 20 , 21 For each sample, levels of ROS were expressed in terms of DCF fluorescence generation/ mg protein/ min.…”
Section: Methodsmentioning
confidence: 99%
“…PTE has also been shown to be a potent antioxidant drug against various diseases, such as pulmonary fibrosis and cerebral ischemia‐reperfusion 7,8 . Furthermore, several preclinical investigations have also explored PTE's potential in preventing cardiac disorders 9‐11 . These findings underscores PTE's heightened potency as a modulator of cardioprotection.…”
Section: Introductionmentioning
confidence: 99%